Speech Development Pattern Strategy in Indonesian Language Teaching Practices by PPG Students Daljab PGRI - Ida Ayu Agung Ekasriadi; I Kadek Adhi Dwipayana; Ni Luh Gede Liswahyuningsih (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
The teacher acts as the main communicator in the classroom, using spoken language to convey material, motivate students, and create a conducive learning environment. However, many teachers, especially Indonesian language teachers, still need to fully understand the importance of skills in learning, resulting in their speaking skills being low. This study aims to analyze the strategies of speech development patterns as well as the reasons and purposes of their application in Indonesian language teaching practice by PPG Daljab K1 students. This research is classified into case study research. The data source is in the form of learning videos uploaded to each PPG Daljab student's YouTube account, totaling 36 data. Data collection is done using observation and interview methods. The instrument used is an interview sheet. After the data was collected, it was analyzed through several stages, including three stages, namely data reduction, data presentation, and conclusion drawing or verification. The main results of this study show that PPG Daljab students use various strategies of speech development patterns, such as deductive, inductive, causal, logical, direct comparison, basic techniques of explanation before or after the statement, analogy, narration, and climax, in the practice of teaching Indonesian. This study concludes that the use of this strategy creates an effective learning situation, allowing students to develop mental and intellectual activities to the fullest. The implication of this study suggests the importance of integrating this strategy into the educational curriculum to improve the effectiveness of Indonesian language learning at the PPG Daljab level.